2022
DOI: 10.3389/fmed.2021.793990
|View full text |Cite
|
Sign up to set email alerts
|

Low Birthweight as a Risk Factor for Non-communicable Diseases in Adults

Abstract: According to studies undertaken over the past 40 years, low birthweight (LBW) is not only a significant predictor of perinatal death and morbidity, but also increases the risk of chronic non-communicable diseases (NCDs) in adulthood. The purpose of this paper is to summarize the research on LBW as a risk factor for NCDs in adults. The Barker hypothesis was based on the finding that adults with an LBW or an unhealthy intrauterine environment, as well as a rapid catch-up, die due to NCDs. Over the last few decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 59 publications
0
27
0
7
Order By: Relevance
“…Last, we found dysregulation in gene networks related to inflammation and immune regulation in cases. Collectively, our findings suggest that the placental transcriptome is altered in fetuses with SB, and that placental dysfunction in fetuses with SB may, in part, underlie poor fetal growth, and contribute to subsequent comorbidities 54 and increased risk of mortality 55 .…”
Section: Discussionmentioning
confidence: 75%
“…Last, we found dysregulation in gene networks related to inflammation and immune regulation in cases. Collectively, our findings suggest that the placental transcriptome is altered in fetuses with SB, and that placental dysfunction in fetuses with SB may, in part, underlie poor fetal growth, and contribute to subsequent comorbidities 54 and increased risk of mortality 55 .…”
Section: Discussionmentioning
confidence: 75%
“…The gestational age at diagnosis is used to further subdivide FGR into early-onset, detected before 32 weeks of gestation, and late-onset according to international consensus (7). Neonates born following FGR have an increased risk of developing health problems, both in the immediate postnatal period including low blood sugars and poor temperature regulation and feeding, but also in later adult life in the form of cardiovascular and metabolic disease (8, 9). Management of pregnancies affected by FGR can be challenging, as timing of delivery needs to be judged well, to balance the hazards of preterm birth against the risks of irreversible damage secondary to intrauterine hypoxia and nutritional deficiency or even stillbirth (10).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies confirmed that LBW is strongly associated with a higher risk of neonatal death, stunting, lower academic performance, mental health, and some non-communicable diseases (NCDs) including type 2 diabetes mellitus, hypertension, and cardiovascular diseases (CVDs) in later life. [1][2][3][4][5] The global prevalence of LBW is estimated at 14.6 to 20% of all live births, of which almost 95.6% are in developing countries. It is also associated with 60 to 80% of neonatal deaths worldwide.…”
Section: Introductionmentioning
confidence: 99%